Kelimpahan dan Prevalensi Endoparasit pada Ikan Jangki (Famili Lethrinidae) dari Pasar Ikan Kedonganan - Kastuwiharja, Putu Stephanie; Julyantoro, Pande Gde Sasmita; Pebriani, Dewa Ayu Angga (Current Trends in Aquatic Science; Vol 7 No 2 (2024), 2025)
The emperor fish (Family Lethrinidae) is one of the most demanded fish in the world, also found covers Indonesian coastal and Indo-Pasific waters. As a country that exported the emperor fish to several countries such as Australia, Asia, and several countries in Middle East, it should be our concern to the quality of the fish. Abundance and prevalence are used as the parameters to ascertain the quality of the fish. Based on that reason, the purpose of this research is to get information on the parasite’s abundance and prevalence in the fish that could affect the quality of Emperor fish in Kedonganan Fish Market. This research uses the quantitative descriptive method with 30 random fish samples from the Kedonganan Fish Market. From the result of the research, the examination of the intestine and stomach of the fish showed the abundance of Lecithocladium is 2,7 ind/fish of 25 samples, and the abundance of Anisakis is 1,63 ind/fish of 20 samples. The prevalence of Lecithocladium is in high level infection (83,80%), and the prevalence of Anisakis is in medium level infection (66,60%). Lecithocladium and Anisakis only found in 28 of 30 samples in the research.